Family in the context of resocialization pedagogy - Raszková, Tereza; Hoferková, Stanislava (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The family as a socializing factor stands in the centre of interest of many disciplines, including social and re-social pedagogy. It is one of the most important external factors within the etiology of social deviance; dysfunctional family environment is usually one of the main causes of behavioural disorders. Inter-generational crime, abuse of addictive substances by family members, neglect and abuse, unemployment and social exclusion often appear in the anamnesis of delinquent individuals; educational problems occur in childhood. The family is also an important and often neglected factor in the re-socialization and re-integration of delinquent individuals. It plays a crucial role in the “remedy” and resocialization of individuals in all types of etopedical care facilities – in children's homes with schools, youth detention institutes, educational care centres or in prison (criminal measures), as well as in the treatment by a curator (social curator or curator for children and juveniles), or a probation and mediation officer (probation program, probation supervision). In detention facilities within the penitentiary practice contact with the family is a part of rehabilitation programs, so-called treatment programs. Support of the relationship with the family is also one of the fundamental rights of the convict. In the penitentiary process the family is one of the biggest motivating factors; it may be helpful in the implementing of treatment programs and it helps to maintain the good mental health of convicts. But the family may also represent a negative factor, e.g. in a case of the introduction of illegal goods into prisons or in the case of further negative and undesirable effects on the individual (e.g. inter-generational crime).
Keywords: family; pedagogy of resocialization; resocialization; prison